The Complete Sequence of the Acacia ligulata Chloroplast Genome Reveals a Highly Divergent clpP1 Gene. - Williams, A.; Boykin, L.; Howell, K.; Nevill, Paul; Small, I. (Public Library of Science, 2015)
Legumes are a highly diverse angiosperm family that include many agriculturally important species. To date, 21 complete chloroplast genomes have been sequenced from legume crops confined to the Papilionoideae subfamily. Here we report the first chloroplast genome from the Mimosoideae, Acacia ligulata, and compare it to the previously sequenced legume genomes. The A. ligulata chloroplast genome is 158,724 bp in size, comprising inverted repeats of 25,925 bp and single-copy regions of 88,576 bp and 18,298 bp. Acacia ligulata lacks the inversion present in many of the Papilionoideae, but is not otherwise significantly different in terms of gene and repeat content. The key feature is its highly divergent clpP1 gene, normally considered essential in chloroplast genomes. In A. ligulata, although transcribed and spliced, it probably encodes a catalytically inactive protein. This study provides a significant resource for further genetic research into Acacia and the Mimosoideae. The divergent clpP1 gene suggests that Acacia will provide an interesting source of information on the evolution and functional diversity of the chloroplast Clp protease complex.